Pentingnya Gizi Seimbang dan Stimulasi 1000 Hari Pertama Kehidupan Untuk Mengurangi Gizi Kurang Balita - Achmad, Musfirah; Togubu, Diana Mirza (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2023)
Nutrition and health problems are problems that are still an iceberg phenomenon in Indonesia. This community service program is expected to increase public knowledge and insight into the importance of nutrition, immunization, and stimulation in the first 1000 days of life, reduce the number of malnutrition in toddlers and fulfill health facilities and infrastructure. The community service program will address the importance of nutrition, immunization, and stimulation in the first 1000 days of life for health, multiple intelligences, and reducing malnutrition rates in toddlers. The results of the implementation of this program are an increase in public knowledge that can be measured by pretest and posttest results, a reduction in the number of malnutrition in toddlers, which can be measured by conducting mobile posyandu and monitoring nutritional status, increasing the intelligence of multiple children by conducting KPSP (Pre-Developmental Screening Questionnaire) and direct park simulation of children, improving health degrees through nutrition consultations, the implementation of health facilities and infrastructure through advocacy, as well as the implementation of TOT to puskesmas staff, village midwives, and village cadres for the sustainability of our program